2012
DOI: 10.1016/j.energy.2011.10.050
|View full text |Cite
|
Sign up to set email alerts
|

A framework for environmental assessment of CO2 capture and storage systems

Abstract: Carbon dioxide capture and storage (CCS) is increasingly seen as a way for society to enjoy the benefits of fossil fuel energy sources while avoiding the climate disruption associated with fossil CO 2 emissions. A decision to deploy CCS technology at scale should be based on robust information on its overall costs and benefits. Life-cycle assessment (LCA) is a framework for holistic assessment of the energy and environmental footprint of a system, and can provide crucial information to policymakers, scientists… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(31 citation statements)
references
References 41 publications
(59 reference statements)
0
31
0
Order By: Relevance
“…Previous studies have demonstrated that life-cycle assessment (LCA) is a powerful tool to define the emissions associated with individual CCS plants and other energy systems (Doctor et al, 1993;Koornneef et al, 2008;Odeh and Cockerill, 2008c;Pehnt and Henkel, 2009;Sathre et al, 2012;Spath and Mann, 2004;Viebahn et al, 2007). Tzimas et al (2007) provided insight regarding potential trade-offs between increased emissions of acid pollutants and decreased CO 2 emissions when CCS is implemented, suggesting that NO X emissions might be amplified across the power generation sector.…”
Section: Carbon Capture and Storage And The Environmentmentioning
confidence: 99%
“…Previous studies have demonstrated that life-cycle assessment (LCA) is a powerful tool to define the emissions associated with individual CCS plants and other energy systems (Doctor et al, 1993;Koornneef et al, 2008;Odeh and Cockerill, 2008c;Pehnt and Henkel, 2009;Sathre et al, 2012;Spath and Mann, 2004;Viebahn et al, 2007). Tzimas et al (2007) provided insight regarding potential trade-offs between increased emissions of acid pollutants and decreased CO 2 emissions when CCS is implemented, suggesting that NO X emissions might be amplified across the power generation sector.…”
Section: Carbon Capture and Storage And The Environmentmentioning
confidence: 99%
“…Yet, even if global emissions were to peak in 2015, and accounting for population and economic growth, the world economy would need to reduce that carbon intensity by 7 percent a year-that is, ten times faster than it actually is-to have a reasonable chance of not raising average temperature by more than 2 °C (Jackson 2009). Furthermore, emission reductions expected from energy efficiency policies and carbon capture and storage systems are likely overestimated, mostly due to the energy penalty of some of those technologies, their scaling-up, non-CO 2 pollution, rebound effect on actual demand, transition costs, and vested interests (Arvesen, Bright, and Hertwich 2011;Sathre et al 2011; see also Jacobson 2009). As Jackson (2009, 83) points out, technological breakthroughs in energy generation, sequestration, or geo-engineering are not impossible, and could very well come from nanotechnology and synthetic biology (see also ETC Group 2004;Kunstler 2005;Hällström 2008).…”
Section: Assumptions About Mitigationmentioning
confidence: 99%
“…As a result, carbonation processes should be critically assessed under different operating conditions. Since the LCA framework was utilized for evaluation of system-wide energy and environmental footprints of CCS technology deployment (Sathre et al, 2012), LCA should be employed to assess the environmental impacts of various carbonation processes.…”
Section: Criteria For Technology Assessmentmentioning
confidence: 99%
“…According to ISO 14040, the procedures for implementing LCA include (1) definition of goal and scope, (2) life cycle inventory (LCI), (3) life cycle impact assessment (LCIA), and (4) data interpretation. The key issues such as energy penalty, scale-up challenges, non-climate environmental impacts, uncertainty management, policy-making needs, and market effects should be considered in LCA (Pehnt and Henkel, 2009;Sathre et al, 2012;Viebahn et al, 2012).…”
mentioning
confidence: 99%